Combined effect of traditional Chinese herbal-based formulations Jing Si herbal tea and Jing Si nasal drop inhibits adhesion and transmission of SARS-CoV2 in diabetic SKH-1 mice - Chiang, Chien-Yi; Kuo, Wei-Wen; Lin, Yu-Jung; Kuo, Chia-Hua; Shih, Cheng-Yen; Lin, Pi-Yu; Lin, Shinn-Zong; Ho, Tsung-Jung; Huang, Chih-Yang; Shibu, Marthandam Asokan (Frontiers in Pharmacology, 2022)
Multiple studies show increased severity of SARS-CoV2-infection in patients with comorbidities like hypertension and diabetes. In this study we have prepared two herbal based formulations, a pleiotropic herbal drink (Jin Si Herbal Tea, JHT) and a nasal drop (Jin Si nasal drop, JND), to provide preventive care against SARS-CoV2 infection. The effect of JHT and JND were determined in SARS-CoV2-S-pseudotyped lentivirus infected bronchial and colorectal cell lines and in SKH-1 mice models. For preliminary studies, ACE2 receptor abundant bronchial (Calu-3) and colorectal cells (Caco-2) were used to determine the effect of JHT and JND on the host entry of various variants of SARS-CoV2-S-pseudotyped lentivirus. A series of experiments were performed to understand the infection rate in SKH-1 mice (6 week old, n=9), find the effective-dosage of JHT and JND and determine the combination effect of JHT and JND on the entry and adhesion of various variant SARS-CoV2-S-pseudotyped lentiviruses which included highly transmissible delta and gamma mutants. Further the effect of combined JHT and JND was determined on diabetes induced SKH-1 mice against the comorbidity associated intense viral entry and accumulation. In addition, the effect of combined JHT and JND administration on viral transmission from infected SKH-1 mice to uninfected cage mate mice was determined. The results show that both JHT and JND were effective in alleviating the viral entry and accumulation in the thorax and the abdominal area. While JHT showed a dose dependent decrease in the viral load, JND showed early inhibition of viral entry from day one of the infection. Combined administration of 48.66 mg of JHT and 20 µL of JND showed rapid reduction in the viral entry and reduced the viral load (97-99%) in the infected mice within 3 days of treatment. Moreover, 16.22 mg of JHT and 20 µL JND reduced the viral infection in STZ induced diabetic SKH-1 mice. Interestingly, combined JHT and JND also inhibited the viral transmission among cage mates. The results therefore show that combined administration of JHT and JND is a novel and an efficient strategy to potentially prevent SARS-CoV2 infection.